Morpho-phylogenetic evidence for the first freshwater record of Trichoderma protrudens Samuels & P. Chaverri (Hypocreales, Sordariomycetes) - Bernard Paul S. Dangallo; Jan Felnesh Exe V. Bagacay; Carr Marlo Canto; Jasmine C. Velo; Mark S. Calabon (Check List)
Trichoderma protrudens Samuels & P. Chaverri was originally described from the trunk of Theobroma cacao L. in Kerala, India, in 2008. Morphologically, it is defined by trichoderma‑like conidiophores bearing subulate or lageniform phialides, green subglobose to obovoidal conidia, and the presence of chlamydospores in culture. Multilocus phylogenetic analyses based on ITS, rpb2, and tef1-α sequence data confirmed the iden‑ tity of the isolates from the Philippines as T. protrudens, with robust support values (100% ML, 1.00 BPP) clustering them with the holotype CBS 121320. This study represents the first global record of T. protrudens in a freshwater ecosystem, expanding this species’ known ecological range into aquatic environments. These findings emphasize the ecological versatility of T. protrudens and underscore the importance of further investigations into the fungal diversity of freshwater habitats.